Efficacy and tolerance of everolimus in 123 consecutive advanced ER positive, HER2 negative breast cancer patients. A two center retrospective study. Issue 6 (December 2015) - Chocteau-Bouju, D.; Chakiba, C.; Mignot, L.; Madranges, N.; Pierga, J.-Y.; Beuzeboc, P.; Quenel-Tueux, N.; Dieras, V.; Bonnefoi, H.; Debled, M.; Cottu, P.
Abstract: Background: Since the publication of the Bolero-2 trial, everolimus has entered the routine care for advanced endocrine resistant luminal breast cancer (BC). We evaluated our practice 2 years after the French marketing authorization (July 2012). Methods: One hundred and twenty three consecutive patients were treated with everolimus combined with endocrine treatment in two French Cancer Centers. All patients had luminal (ER positive, HER2 negative) BC and had been previously treated with endocrine therapy for advanced disease. Results: Median age at initiation of everolimus was 63 y (36–84). Median delay from cancer diagnosis to everolimus was 12.6 y (1.3–34.8). Grade 2 or 3 side effects were experienced by 49.6% and 32.5% of the patients, respectively. Most frequent side effects were grade 2/3 mucositis (32.6%/11.2%), grade 1/2 decreased appetite (24.4%/13.8%), and grade 1/2 rash (28.5%/13.8%). At a median follow up of 10 months, median progression free survival was 9 months (0.4–26+), and median overall survival was 21 months (0.4–26+). Conclusions: In routine practice everolimus efficacy appears very close to the Bolero-2 results, although in more heavily pretreated patients. Everolimus based therapy appears feasible and side effects are similar to those previously reported. These data support the use of everolimus in daily practice.